Refugees and local power dynamics: The case of the Gambella Region of Ethiopia - Samuel Zewdie Hagos (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The Gambella Region is one of the marginalised and most conflict-ridden regions in Ethiopia. Recently, violent clashes between the two largest ethnic groups in the region - the host communities, the Anywaa, and the South Sudanese Nuer refugees - have reignited the debate on refugee integration in the region. In fact, the roots of the Anywaa-Nuer conflict can be traced back to the imperial regime of Ethiopia at the end of the 19th century. In the early 1960s however, the arrival and spontaneous integration of Nuer refugees was peaceful and relations between both ethnic groups were harmonious. During this time, refugee management was organised locally. Against this background, the focus of the present paper is to understand the nature, context and evolution of the long-standing conflict between the Anywaa and refugees from the Nuer ethnic group in the Gambella Region. Beyond that, the paper explores the Anywaa-Nuer conflict within the context of the political power dynamics of the last two decades. Thereby, the paper reveals that the disputes between the Anywaa and the Nuer have taken on a new dimension since the early 1990s.
Keywords: 330; Ethnische Beziehungen; Flüchtlinge; Bevölkerung; Soziale Integration; Äthiopien